Individual, interpersonal, and organisational factors of healthcare conflict: A scoping review. Issue 3 (4th May 2017) - Kim, Sara; Bochatay, Naike; Relyea-Chew, Annemarie; Buttrick, Elizabeth; Amdahl, Chris; Kim, Laura; Frans, Elise; Mossanen, Matthew; Khandekar, Azhar; Fehr, Ryan; Lee, Young-Mee
ABSTRACT: Unresolved conflicts among healthcare professionals can lead to difficult patient care consequences. This scoping review examines the current healthcare literature that reported sources and consequences of conflict associated with individual, interpersonal, and organisational factors. We identified 99 articles published between 2001 and 2015 from PubMed, Cumulative Index to Nursing and Allied Health Literature, and Excerpta Medical Database. Most reviewed studies relied on healthcare professionals' perceptions and beliefs associated with conflict sources and consequences, with few studies reporting behavioural or organisational change outcomes. Individual conflict sources included personal traits, such as self-focus, self-esteem, or worldview, as well as individuals' conflict management styles. These conflicts posed threats to one's physical, mental, and emotional health and to one's ability to perform at work. Interpersonal dynamics were hampered by colleagues' uncivil behaviours, such as low degree of support, to more destructive behaviours including bullying or humiliation. Perceptions of disrespectful working environment and weakened team collaboration were the main interpersonal conflict consequences. Organisational conflict sources included ambiguity in professional roles, scope of practice, reporting structure, or workflows, negatively affecting healthcare professionals' job satisfactions and intent to stay. Future inquiries into healthcare conflict research may target the following: shifting from research involving single professions to multiple professions; dissemination of studies via journals that promote interprofessional research; inquiries into the roles of unconscious or implicit bias, or psychological capital (i.e., resilience) in healthcare conflict; and diversification of data sources to include hospital or clinic data with implications for conflict sources.